Knee disarticulation - Antun Muljačić; Ognjen Živković; Renata Poljak-Guberina (Medicinski Glasnik, 2009)
In this paper we presented three patients withknee disarticulation performed according toBaumgartner. The Baumgartner tehnique and theapplication of knee disarticulation prosthesis appearedto be superior in comparisson with othermethods.